1995
DOI: 10.3109/10428199509054756
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 and Tumor Necrosis Factor Alpha Induce Class 1 Aldehyde Dehydrogenase mRNA and Protein in Bone Marrow Cells

Abstract: Interleukin-1 (IL-1) and tumor necrosis factor alpha (TNF alpha) protect normal human hematopoietic progenitors from the toxicity of 4-hydroperoxycyclophosphamide (4-HC). Aldehyde dehydrogenase Class 1 (ALDH-1) is the enzyme that inactivates 4-HC. Diethylaminobenzaldehyde (DEAB), a competitive inhibitor of ALDH-1, was shown to prevent the protective effects of IL-1 and TNF alpha. In this study, we examined the effect of IL-1 and TNF alpha on the expression of ALDH-1 in normal bone marrow as well as malignant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
3

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 34 publications
0
13
0
3
Order By: Relevance
“…A possible mechanism for the protection of stem cells from drugs such as 4-HC via ALDH1 may be due to interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α) [104]. Moreb, et al observed that pre-treatment of bone marrow cells with IL-1 and TNF-α for 6 to 20 hours resulted in an increase in ALDH1 mRNA and protein levels [105], and that this ultimately leads cellular protection against 4-HC [104]. Since then, it has been determined that high cytosolic ALDH1A1 or ALDH3A1 activity in normal cells [106,107], stem cells [44], and cancer stem cells [65,74] confers resistance to therapy in preclinical model systems.…”
Section: Aldh Plays a Self-protective Role In Normal Stem Cells And Cscsmentioning
confidence: 99%
“…A possible mechanism for the protection of stem cells from drugs such as 4-HC via ALDH1 may be due to interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α) [104]. Moreb, et al observed that pre-treatment of bone marrow cells with IL-1 and TNF-α for 6 to 20 hours resulted in an increase in ALDH1 mRNA and protein levels [105], and that this ultimately leads cellular protection against 4-HC [104]. Since then, it has been determined that high cytosolic ALDH1A1 or ALDH3A1 activity in normal cells [106,107], stem cells [44], and cancer stem cells [65,74] confers resistance to therapy in preclinical model systems.…”
Section: Aldh Plays a Self-protective Role In Normal Stem Cells And Cscsmentioning
confidence: 99%
“…2 A and B) (32). To test whether BAAA was a substrate for human ALDH, K562 cells were stained with BAAA (28,33). K562 cells stained moderately with BAAA ( Fig.…”
Section: Baaa Is a Substrate For Aldhmentioning
confidence: 99%
“…ALDH is a cytosolic enzyme that is responsible for oxidizing a variety of aldehydes including vitamin A (24,25). ALDH is expressed at high levels in hematopoietic progenitors and appears to be responsible for the resistance of HSCs to the alkylating agents cyclophosphamide and 4-hydroxyperoxycyclophosphamide (10,(26)(27)(28). Jones et al (22,29) demonstrated proof of the principle for this strategy in the murine system.…”
mentioning
confidence: 99%
“…All cell lines were grown in RPMI to be induced by IL-1 and/or TNF␣. 10,11 The overexpression 1640 medium supplemented with 10% fetal calf serum (FCS) of MnSOD and ALDH-1 promotes resistance to radiation and except for HL-60 and KG-1 cells which were grown in IMDM 4-HC, respectively. 12,13 medium supplemented with 20% FCS.…”
mentioning
confidence: 99%